2018
DOI: 10.18036/aubtdc.333248
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity Researching on New Species of Echinops L. (Asteraceae): Antimicrobial and Antioxidant Activity of Echinops Antalyensis

Abstract: The aim of this study was to investigate the antimicrobial and antioxidant activities of different extracts from Echinops antayensis C.Vural. Antimicrobial activity was estimated against several common human pathogenic bacterial strains using the agar disc diffusion and minimum inhibitory concentration assays. Antioxidant activity was evaluated using the DPPH radical-scavenging assay and total phenolic content methods. On the light of these experiments, E. antalyensis would seem to be an important natural anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Plant extracts and essential oils can control microbial growth which depends on the chemical composition which is dependent on the method of extraction and solvent type. Şapci and Vural (2018) indicated that the antimicrobial and antifungal activity of Echinops emiliae extract could be change with the type of used extracts [5]. Besides, they are used in other industries including traditional medicine, dietary supplements, recombinant protein manufacturing and functional foods [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant extracts and essential oils can control microbial growth which depends on the chemical composition which is dependent on the method of extraction and solvent type. Şapci and Vural (2018) indicated that the antimicrobial and antifungal activity of Echinops emiliae extract could be change with the type of used extracts [5]. Besides, they are used in other industries including traditional medicine, dietary supplements, recombinant protein manufacturing and functional foods [14].…”
Section: Resultsmentioning
confidence: 99%
“…There are few researches on the antimicrobial activity of Echinops genius. Şapci and Vural (2018) studied antimicrobial and antioxidant activity of Echinops antalyensis [5]. The research of Gemechu et al (2016) was on the antimicrobial activity of Echinops kebericho against human pathogenic bacteria and fungi [6].…”
Section: Introductionmentioning
confidence: 99%